Transformative Learning Experiences of International Graduate Students from Africa - Kumi-Yeboah, Alex (Journal of International Students, 2014)
This article examines factors that influence transformative learning experiences of international graduate students from Africa. In general, 84.8% of the participants experienced transformative learning while 15.2% reported no transformative experiences. For those who experienced transformative learning, 26.1% of the transformative experiences were associated with education, 28.3% by non-education, and 30.4% were by both education and non-education. Follow-up interviews were conducted from 12 participants who were randomly selected to ensure representations across gender, age group, country of origin, and program of study. They identified classroom activities, faculty support, and learning a new language as the educational transformative learning, and factors related to new life experiences, as non-educational. Field notes and reflection journals were utilized to triangulate data to support these methods. Data analysis and results of the study indicate that participants experienced transformative learning through both educational and non-educational related activities.